Audit fees, patent litigation, and long-term performance - Ya-Fang Wang (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: The business risk of patent litigation contributes to auditors' professional skepticism and thereby results in different audit pricing decisions. Patent infringement is viewed as a specific news and thereby results in different economic consequences. This study examines the association among auditor reaction, patent litigation, and long-term economic consequences by exploring the different patent infringement cases. Design/methodology/approach: This study adopts a regression model to examine my research issues. Finding: The empirical results suggest that, (1) auditors consider patent settlement as a risk factor in the evaluation of business risks and lead to higher audit fees and lower business risk; (2) overseas patent litigation may affect auditors' perceived risk of patent litigation and lead to higher audit fees and lower business risk; (3) relative to Plaintiff companies, auditors perceive Defendant companies have a higher business risk and lead to higher audit fees and lower business risk; (4) relative to companies without overseas litigation, auditors perceive companies with overseas litigation have a higher business risk and lead to higher audit fees and lower business risk; (5) Defendant companies have the advantage of long-term growth performance within 3 years after settlement negotiations of patent litigation; (6) settlement negotiations would be a significant moderator for overseas patent litigation, and companies are more likely to obtain a favorable long-term performance. Research limitations/implications: Research data is obtained from three different sources: First, the lawsuit information was hand-collected from the Market Observation Post System (MOPS). Second, the patent-related information was hand-collected from the Taiwan Patent Search System (TPSS). Third, audit fees and accounting data were obtained from the Taiwan Economic Journal (TEJ) database. Therefore, hand-collected data and lack of audit fees data restrict the research sample to a manageable size. The number of observations during the period 2010-2020, which totals 307 observations. Originality/value: This study differs from previous studies in focusing on patent litigation cases to examine the association among auditor reaction, patent litigation, and long-term economic consequences by investigating whether auditors and market participants charge risk premiums for companies with the potential business risk of uncertain patent litigation, because potential business risk for patent litigation matters to market participants, and assessments of the perception of business risk can potentially provide useful and timely information to investors, auditors, and regulatory.
Keywords: M41; M42; 330; Patent Litigation; Audit Fees; Long-Term Performance